2020
DOI: 10.1111/iej.13319
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dentine cutting efficiency on the lateral force created by torque‐controlled rotary instruments

Abstract: AIM To study the impact of dentine cutting efficiency of rotary instruments on the lateral force they create when instrumenting simulated root canals in bovine dentine. METHODOLOGY Lateral cutting efficiency of austenitic files (ProTaper Universal) was compared to that of counterparts of a reported identical geometrical design with a martensite phase component (ProTaper Gold) in bovine dentine disks (n = 6). Instrument shapes were studied using digital microscopy. The intracanal lateral force exerted by the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Since the highest forces were provoked close to the working length (Tables 2 and 3), caution is advised when preparing the apical third with thin dentinal walls when large taper and wide-diameter instruments are applied. The rotary instrumentation ndings align with previous studies [27]. Another in vitro study concluded that the low fracture threshold of mandibular incisor roots during an obturation procedure was 1.5 kg or 14.7 N [11].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Since the highest forces were provoked close to the working length (Tables 2 and 3), caution is advised when preparing the apical third with thin dentinal walls when large taper and wide-diameter instruments are applied. The rotary instrumentation ndings align with previous studies [27]. Another in vitro study concluded that the low fracture threshold of mandibular incisor roots during an obturation procedure was 1.5 kg or 14.7 N [11].…”
Section: Discussionsupporting
confidence: 86%
“…Sample sectioning and mounting for the testing platform. The samples were prepared according to a previously published methodology [27]. In short, the teeth were decoronated with a slow-speed round diamond disk at the cementoenamel junction (CEJ) level on the interproximal aspect, leaving approximately 2 mm of coronal tooth structure on the buccal and lingual aspects (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometric pattern of the endodontic instruments, the technique used, and the shape of the root canal (straight or curved) are important factors in achieving optimal treatment. As mentioned above, the root canal has three portions (coronal, middle, and apical) and, according to studies conducted on a tooth with a straight root canal, the highest stress occurs in the apical portion [ 41 , 42 ], constituting a disadvantage in the endodontic treatment of canine 3.3. There must be a close connection between the materials used for the treatment to give an optimal result.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies have a major drawback, which is the inability to eliminate several confounding parameters other than a single variable of interest, resulting from the difference in multiple parameters among the brands being tested. Thus, some studies have compared instruments with the same geometry but different heat-treatment [22,24,25]. In this regard, to the best of our knowledge, no studies to date have definitively proven the impact of the radial land on the shaping performance of NiTi rotary instruments.…”
Section: Sample Size Calculationmentioning
confidence: 99%